Model Debit Sedimen Suspensi Penggunaan Lahan Permukiman pada Bentang Lahan Gunungapi - Hadini, La Ode; Hidayat, Ahmad; Aba, La (LaGeografia, 2023)
Sediment flows in volcanic landscapes are sensitive to land uses. Settlements of land use are often found along the slopes of volcanoes in Indonesia. Many detailed studies of sediment discharge in agroforestry and dryland in volcanic slopes have been carried out. Meanwhile, the settlement's land use is not of interest to researchers. This study aims to build a model of sediment discharge in settlement areas of volcanic landscapes with a focus on (1) the relationship between sediment discharge and water flow discharge; and (2) the sediment rate and soil loss in settlement land use. The study used the key area method in watershed areas that have settlements land use. The research was carried out using field surveys to observe soil, slope morphology, and the settlement's land cover characteristics. Sediment flow was measured in the suspended sediment data and bedload sediment. Water flow data was measured in the canal water level and the rain data was measured with an automatic water level recorder and the Automatic Rain Recorder, as well as field observations of the characteristics of the flows entering the canal system. Data analysis was carried out to produce a model of sediment discharge, and the rate of soil loss. The research resulted in a suspension discharge Qs=0.4396Q1.2123 and a soil loss rate of 5.04 tons/year.AbstrakAliran sedimen bentanglahan gunungapi sensitif terhadap bentuk-bentuk penggunaan lahannya. Bentuk penggunaan lahan permukiman sudah banyak dijumpai di sepanjang lereng gunungapi di Indonesia. Kajian detil debit sedimen pada penggunaan lahan agroforestry dan tegalan pada bagian lereng gunungapi sudah banyak dilakukan. Sementara, bentuk penggunaan lahan permukiman tidak diminati para peneliti. Penelitian ini bertujuan memangun model debit sedimen di kawasan permukiman bentanglahan gunungapi dengan fokus pada: (1) hubungan debit sedimen dan debit aliran; (2) laju sedimen dan nilai kehilangan tanah pada penggunaan lahan permukiman. Penelitian menggunakan metode area kunci kawasan DAS dengan penggunaan lahan permukiman. Penelitian dilakukan dengan survey lapangan untuk pengamatan tanah, morfologi lereng, dan karakteristik penutupan lahan di permukiman. Aliran sedimen diukur berupa data sedimen suspensi dan sedimen dasar. Data aliran air diukur berupa tinggi muka air saluran dan data hujan diukur dengan automatic water level recorder dan Automatic Rain Recorder, serta pengamatan lapangan karakteristik alur aliran air yang masuk ke dalam sistem saluran. Analisis data dilakukan untuk menghasilkan model debit sedimen dan laju kehilangan tanah yang terjadi. Penelitian menghasilkan debit suspensi Qs=0,4396Q1,2123 dan laju kehilangan tanah 5,04 ton/thn.